(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

verify the equation is homogeneous and solve.. thanks

(x^2 - 2y^2)dx + (xy)dy = 0

(x^2 - 2y^2) = -(xy)dy/dx

(x^2 - 2y^2)/-(xy) = dy/dx

-(x/y) - 2(y/x) = dy/dx

v = (y/x) .. y = vx and dy/dx = v + xv'

-(1/v) - 2v = v + xv'

x(dv/dx) + (1/v) + 3v = 0

3v + (1/v) = -x(dv/dx)

(3v + (1/v))/dv = -x/dx

(1/3v + v)dv = (1/x) dx

1/9v^3 + 1/2v^2 = ln|x| + c

2. Relevant equations

3. The attempt at a solution

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Please check my work: verify that the equation is homogeneous

Can you offer guidance or do you also need help?

**Physics Forums | Science Articles, Homework Help, Discussion**